Longitudinal behavioral analysis during dental care of children aged 0 to 3 years - Cunha, Robson Frederico [UNESP]; Zaze, Ana Carolina Soares Fraga [UNESP]; Vieira, Ana Elisa de Mello; Melhado, Fabíola Lemos; Sundefeld, Maria Lúcia Marçal Mazza [UNESP] (FapUNIFESP (SciELO), 2009)
Abstract: When and how the dentist intervenes have repercussions on children's physical and emotional patterns. The objective of the present study was to conduct a longitudinal behavioral analysis during dental care of babies aged 0 to 3 years. A total of 216 patients seen at the Baby Clinic of the School of Dentistry at Araçatuba, São Paulo State University (UNESP), were selected. The selection criterion was attendance at ten dental care sessions at bimonthly intervals for routine procedures such as clinical examination and oral hygiene. There was a predominance of cooperative behavior compared to uncooperative behavior when each visit was analyzed separately. The behavior of the patients must have been directly influenced by their psychomotor development. Constant attendance and exposure of the baby to non-stressful dental stimuli are factors that favor a cooperative behavior.
Keywords: Behavior; Child; Dental care; child behavior; cooperation; dental care; doctor patient relation; female; human; infant; longitudinal study; male; mouth hygiene; newborn; patient compliance; physical examination; preschool child; psychological aspect; statistics; Child Behavior; Child, Preschool; Cooperative Behavior; Dental Care; Dentist-Patient Relations; Female; Humans; Infant; Infant Behavior; Infant, Newborn; Longitudinal Studies; Male; Oral Hygiene; Patient Compliance; Physical Examination